Surface protective film

JP2025032992APending Publication Date: 2025-03-12NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024140636
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-28
Filing Date
2024-08-22
Publication Date
2025-03-12

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、優れた軽剥離性と優れた低汚染性を発現できる表面保護フィルムを提供することできる。また、本発明によれば、そのような表面保護フィルムを含む光学部材や電子部材を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025032992000001_ABST
    Figure 2025032992000001_ABST
Patent Text Reader

Abstract

To provide a surface protective film capable of exhibiting excellent light detachability and excellent low contamination, and also to provide an optical member and an electronic member including the surface protective film.SOLUTION: A surface protective film includes a base material and an adhesive layer. The adhesive layer includes an urethane-based adhesive agent. The urethane-based adhesive agent is formed from an urethane-based adhesive composition. The urethane-based adhesive composition includes a base polymer (A), a polyfunctional isocyanate compound (B) and a silicone-based compound (C). The base polymer (A) includes an urethane prepolymer. The silicone-based compound (C) has a skeleton derived from a monomer (a) whose corresponding homopolymer has Tg of 80°C or higher.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a surface protection film. [Background technology]

[0002] In the manufacturing process of optical or electronic components, a surface protection film having a base material and a pressure-sensitive adhesive layer is generally attached to the exposed surface of the optical or electronic component to prevent the surface of the optical or electronic component from being scratched during processing, assembly, inspection, transportation, etc. Such a surface protection film is peeled off from the optical or electronic component when surface protection is no longer necessary (Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 6613516 Summary of the Invention [Problem to be solved by the invention]

[0004] When attempting to peel the surface protection film from an optical or electronic component to which it is attached, it is important that the surface protection film can be peeled off smoothly only at the interface between the surface protection film and the optical or electronic component, and the surface protection film is required to have excellent easy peelability.

[0005] In addition, optical and electronic components are generally expensive and easily damaged, and therefore it is important that the surface protection film attached to the exposed surface of an optical or electronic component does not damage the optical or electronic component when peeled off, and from this point of view, excellent easy peelability is also required.

[0006] On the other hand, after a surface protective film is peeled off from an optical member or electronic member to which the surface protective film is attached, the surface of the optical member or electronic member is easily contaminated by components contained in the pressure-sensitive adhesive layer of the surface protective film, and as a result, the adhesion of other layers to the surface is reduced, and problems such as the other layers being easily peeled off from the surface are likely to occur. From this viewpoint, the surface protective film is required to have excellent low-contamination properties.

[0007] An object of the present invention is to provide a surface protection film that exhibits excellent easy peelability and excellent low staining properties, and to provide an optical member or an electronic member that includes such a surface protection film. [Means for solving the problem]

[0008] [1] A surface protection film according to an embodiment of the present invention is a surface protection film including a substrate and an adhesive layer, the adhesive layer being composed of a urethane-based adhesive, the urethane-based adhesive being formed from a urethane-based adhesive composition, the urethane-based adhesive composition including a base polymer (A), a polyfunctional isocyanate compound (B) and a silicone-based compound (C), the base polymer (A) including a urethane prepolymer, and the silicone-based compound (C) being a silicone-based compound having a skeleton derived from a monomer (a) whose corresponding homopolymer has a Tg of 80°C or higher. [2] In the surface protective film described in [1] above, the equivalent ratio ([NCO] / [OH]) of the NCO group of the polyfunctional isocyanate compound (B) to the OH group of the urethane prepolymer may be 1.0 or more. [3] In the surface protective film according to the above [1] or [2], the equivalent ratio ([NCO] / [OH]) of the NCO group of the polyfunctional isocyanate compound (B) to the OH group of the urethane prepolymer may be 4.6 or less. [4] In the surface protective film according to any one of [1] to [3] above, the content of the silicone compound (C) in the urethane-based pressure-sensitive adhesive composition may be 0.7 parts by weight or less per 100 parts by weight of the base polymer (A). [5] An optical member according to an embodiment of the present invention includes the surface protection film according to any one of [1] to [4] above. [6] An electronic device according to an embodiment of the present invention includes a surface protection film according to any one of [1] to [4] above. Effect of the Invention

[0009] According to the present invention, it is possible to provide a surface protection film that exhibits excellent easy peelability and excellent low staining properties. Furthermore, according to the present invention, it is possible to provide an optical member or an electronic member including such a surface protection film. [Brief description of the drawings]

[0010] [Figure 1] 1 is a schematic cross-sectional view of a surface protection film according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] When the term "weight" appears in this specification, it may be read as "mass," which is the commonly used SI unit for indicating weight.

[0012] In this specification, the term "(meth)acrylic" means "acrylic and / or methacrylic", the term "(meth)acrylate" means "acrylate and / or methacrylate", the term "(meth)allyl" means "allyl and / or methallyl", and the term "(meth)acrolein" means "acrolein and / or methacrolein".

[0013] <<A. Surface protection film>> The surface protection film according to the embodiment of the present invention includes a substrate and a pressure-sensitive adhesive layer. As long as the surface protection film according to the embodiment of the present invention includes a substrate and a pressure-sensitive adhesive layer, it may include any other appropriate member (any other appropriate layer, etc.) within a range that does not impair the effects of the present invention.

[0014] One embodiment of the surface protection film of the present invention comprises a substrate, a pressure-sensitive adhesive layer, and a release liner (also referred to as a release sheet or separator) provided on the surface of the pressure-sensitive adhesive layer opposite the substrate. Another embodiment of the surface protection film of the present invention comprises a substrate and a pressure-sensitive adhesive layer.

[0015] Fig. 1 is a schematic cross-sectional view of a surface protection film according to one embodiment of the present invention. In Fig. 1, a surface protection film 10 includes a substrate 1, a pressure-sensitive adhesive layer 2, and a release liner 3. In Fig. 1, the substrate 1, the pressure-sensitive adhesive layer 2, and the release liner 3 are directly laminated together.

[0016] The thickness of the surface protection film according to the embodiment of the present invention may be any appropriate thickness within a range that does not impair the effects of the present invention. The thickness of the surface protection film according to the embodiment of the present invention is preferably 5 μm to 500 μm, may be 10 μm to 450 μm, may be 15 μm to 400 μm, or may be 20 μm to 300 μm.

[0017] The surface protection film according to the embodiment of the present invention has an acrylic plate peeling force (I) of preferably 3.0 gf / 25 mm or less after being left at a temperature of 23° C. for 30 minutes, and may be 2.5 gf / 25 mm or less, 2.3 gf / 25 mm or less, 2.0 gf / 25 mm or less, 1.8 gf / 25 mm or less, or 1.7 gf / 25 mm or less. If the acrylic plate peeling force (I) is within the above range, the surface protection film according to the embodiment of the present invention can exhibit excellent easy peeling properties. In order to prevent unintended peeling during the manufacturing process, etc., the lower limit of the acrylic plate peeling force (I) is, for example, 0.5 gf / 25 mm or more.

[0018] The above-mentioned peel strength from acrylic plate (I) is the peel strength measured when the pressure-sensitive adhesive layer contained in the surface protection film is attached to the surface of an acrylic plate, left to stand for 30 minutes at a temperature of 23° C., and then the surface protection film is peeled from the surface of the acrylic plate at a peel angle of 180° and a peel speed of 300 mm / min at a temperature of 23° C. A more detailed measurement method will be described later.

[0019] The surface protective film according to the embodiment of the present invention has an acrylic plate peeling force (II) of preferably 10.0 gf / 25 mm or less after being left at a temperature of 50 ° C. for 1 day, and may be 7.0 gf / 25 mm or less, 5.0 gf / 25 mm or less, 4.0 gf / 25 mm or less, 3.0 gf / 25 mm or less, or 2.5 gf / 25 mm or less. If the acrylic plate peeling force (II) is within the above range, the surface protective film according to the embodiment of the present invention can suppress the deterioration of the light peeling property over time. In order to prevent unintended peeling during the manufacturing process, etc., the lower limit of the acrylic plate peeling force (II) is, for example, 0.5 gf / 25 mm or more.

[0020] The above-mentioned peel strength from acrylic plate (II) is the peel strength measured when the pressure-sensitive adhesive layer contained in the surface protection film is attached to the surface of an acrylic plate, left to stand at a temperature of 50° C. for one day, and then the surface protection film is peeled from the surface of the acrylic plate at a peel angle of 180° and a peel speed of 300 mm / min at a temperature of 23° C. A more detailed measurement method will be described later.

[0021] In the surface protection film according to the embodiment of the present invention, the rate of increase in peel strength over time from the peel strength from acrylic plate (I) to the peel strength from acrylic plate (II) (rate of increase in peel strength over time (%)=(peeling strength from acrylic plate (II) / peeling strength from acrylic plate (I))×100(%)) is preferably 250% or less, alternatively 220% or less, 200% or less, 180% or less, 160% or less, 140% or less, 130% or less, or 120% or less. When the rate of increase in peel strength over time is within the above range, the surface protection film according to the embodiment of the present invention can further suppress the decrease in light releasability over time. The lower limit of the rate of increase in peel strength over time is preferably as small as possible, and is, for example, 100% or more.

[0022] The surface protection film according to the embodiment of the present invention has a residual adhesion rate to an acrylic plate of preferably 70% or more, 80% or more, 85% or more, 90% or more, 93% or more, or 95% or more. This residual adhesion rate to an acrylic plate is an index of the extent to which the components of the pressure-sensitive adhesive layer of the surface protection film are transferred to the surface of the adherend and contaminate it. The lower the value of this residual adhesion rate to an acrylic plate, the more contaminated the adherend is, and the higher the value of this residual adhesion rate to an acrylic plate, the more the surface protection film can exhibit excellent low-contamination properties that do not contaminate the adherend. The upper limit value of the residual adhesion rate to an acrylic plate is preferably as high as possible, and is, for example, 100% or less.

[0023] The residual adhesion rate to acrylic plate was measured by attaching an adhesive layer contained in a surface protection film to the surface of an acrylic plate, leaving it at a temperature of 23° C. for 24 hours, peeling the surface protection film from the surface of the acrylic plate at a temperature of 23° C. at a peel angle of 180 degrees and a peel speed of 300 mm / min, attaching an adhesive tape (product name "No. 31B", manufactured by Nitto Denko Corporation, base material thickness: 25 μm, total thickness: 53 μm) to the peeled surface of the acrylic plate, leaving it at a temperature of 23° C. for 30 minutes, and then measuring the residual adhesion rate at a peel angle of 180 degrees and a peel speed of 300 mm / min. The peel force (A) was measured when the sheet was peeled off in 10 minutes, and a similar adhesive tape (product name "No. 31B", manufactured by Nitto Denko Corporation, substrate thickness = 25 μm, total thickness = 53 μm) was attached to the peel surface of an acrylic plate to which the above-mentioned surface protection film had not been attached or peeled off, and after leaving the tape at a temperature of 23°C for 30 minutes, the peel force (B) was measured when the sheet was peeled off at a peel angle of 180 degrees and a peel speed of 300 mm / min, and the residual adhesion rate to the acrylic plate (%) was calculated as (peel force (A) / peel force (B)) x 100 (%). A more detailed measurement method will be described later.

[0024] The surface protective film according to the embodiment of the present invention can be produced by any suitable method. Examples of such a production method include (1) A method in which a material for forming a pressure-sensitive adhesive layer is applied onto a substrate, and then heated and dried as necessary, and cured as necessary; (2) A method in which a material for forming an adhesive layer is applied onto a release liner, and if necessary, heated and dried, and if necessary, cured to form an adhesive layer, and then transferred onto a substrate; (3) A method of forming and coating a pressure-sensitive adhesive layer by extruding a material for forming the pressure-sensitive adhesive layer onto a substrate; (4) A method of extruding a substrate and a pressure-sensitive adhesive layer in two or more layers, (5) A method of laminating a single layer of an adhesive layer on a substrate or a method of laminating a double layer of an adhesive layer together with a laminate layer, (6) A method of laminating a pressure-sensitive adhesive layer with a substrate-forming material such as a film or a laminate layer in two or more layers, The coating method may be any suitable method such as a roll coater method, a comma coater method, a die coater method, a reverse coater method, a silk screen method, or a gravure coater method.

[0025] ≪A-1. Base material≫ The substrate may be a single layer or may be two or more layers. The substrate may be a stretched substrate.

[0026] The thickness of the substrate is preferably from 4 μm to 450 μm, and may be from 8 μm to 400 μm, may be from 12 μm to 350 μm, or may be from 16 μm to 250 μm.

[0027] For the surface of the substrate on which the pressure-sensitive adhesive layer is not applied, a release treatment can be performed by adding, for example, a fatty acid amide, polyethyleneimine, a long-chain alkyl additive, or the like to the substrate in order to form a roll that is easy to unwind, or a coating layer made of any suitable release agent such as a silicone-based, long-chain alkyl-based, or fluorine-based release agent can be provided.

[0028] As the material of the substrate, any suitable material may be adopted depending on the application. For example, plastic, paper, metal film, nonwoven fabric, etc. are included. Plastic is preferable. That is, the substrate is preferably a plastic film. The substrate may be made of one type of material, or may be made of two or more types of materials. For example, it may be made of two or more types of plastic.

[0029] Examples of the plastic include polyester resins, polyamide resins, polyolefin resins, etc. Examples of the polyester resin include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.

[0030] The substrate may contain any suitable additive as necessary. Examples of additives that may be contained in the substrate include antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, fillers, and pigments. The type, number, and amount of additives that may be contained in the substrate may be appropriately set according to the purpose. In particular, when the substrate is made of plastic, it is preferable to contain some of the above additives for the purpose of preventing deterioration. From the viewpoint of improving weather resistance, etc., particularly preferred additives include antioxidants, ultraviolet absorbers, light stabilizers, and fillers.

[0031] <A-2. Adhesive layer> The pressure-sensitive adhesive layer is composed of a urethane-based pressure-sensitive adhesive. The urethane-based pressure-sensitive adhesive is formed from a urethane-based pressure-sensitive adhesive composition. That is, the pressure-sensitive adhesive layer is composed of a urethane-based pressure-sensitive adhesive, and the urethane-based pressure-sensitive adhesive is formed from a urethane-based pressure-sensitive adhesive composition. Typically, the urethane-based pressure-sensitive adhesive formed from the urethane-based pressure-sensitive adhesive composition forms a layer shape to become the pressure-sensitive adhesive layer.

[0032] The pressure-sensitive adhesive layer can be formed by any suitable method. Examples of such methods include a method in which a urethane-based pressure-sensitive adhesive composition is applied onto any suitable substrate, heated and dried as necessary, and cured as necessary to form a pressure-sensitive adhesive layer on the substrate, and a method in which a urethane-based pressure-sensitive adhesive composition is applied onto a release liner, heated and dried as necessary, and cured as necessary to transfer the pressure-sensitive adhesive layer formed on the release liner onto a substrate. The application method, heating and drying conditions, curing conditions, etc. can be appropriately adopted from methods commonly known for forming pressure-sensitive adhesive layers.

[0033] The thickness of the adhesive layer can be appropriately set according to the purpose of the present invention as long as the effect of the present invention is not impaired. The thickness of the adhesive layer is preferably 5 μm to 150 μm, may be 10 μm to 120 μm, may be 20 μm to 110 μm, may be 30 μm to 100 μm, or may be 40 μm to 90 μm.

[0034] In the surface protection film according to the embodiment of the present invention, the urethane-based pressure-sensitive adhesive typically contains a urethane polymer. The urethane polymer in the urethane-based pressure-sensitive adhesive may be of only one type or of two or more types.

[0035] As urethane polymers, generally, there are known "prepolymer type urethane polymers" produced by reacting a urethane prepolymer with a polyfunctional isocyanate compound, and "one-shot type urethane polymers" produced by directly reacting a polyol with a polyfunctional isocyanate compound without using a urethane prepolymer. The urethane prepolymer is typically obtained by reacting a polyol with an excess of a polyfunctional isocyanate compound, and has an isocyanate group at the molecular end. The prepolymer type urethane polymer can be produced by adopting any appropriate method as long as it is a method adopted in the urethane reaction between a urethane prepolymer and a polyfunctional isocyanate compound, within the scope of not impairing the effects of the present invention.

[0036] In the embodiment of the present invention, the urethane polymer contained in the urethane-based pressure-sensitive adhesive is typically a prepolymer type urethane polymer. The prepolymer type urethane polymer may be of only one type, or of two or more types.

[0037] In an embodiment of the present invention, the content of the urethane polymer in the urethane adhesive is preferably 60% by weight to 99.9% by weight, alternatively 70% by weight to 99.9% by weight, 80% by weight to 99.9% by weight, 85% by weight to 99.9% by weight, or 90% by weight to 99.9% by weight, calculated as solid content. When the content of the urethane polymer in the urethane adhesive is within the above range calculated as solid content, the effects of the present invention can be more effectively exhibited.

[0038] In an embodiment of the present invention, the urethane-based pressure-sensitive adhesive composition includes a base polymer (A), a polyfunctional isocyanate compound (B), and a silicone-based compound (C). The base polymer (A) includes a urethane prepolymer. Therefore, in an embodiment of the present invention, the urethane-based pressure-sensitive adhesive composition includes a urethane prepolymer, a polyfunctional isocyanate compound (B), and a silicone-based compound (C).

[0039] The content of the urethane prepolymer in the base polymer (A) is preferably 50% by weight to 100% by weight, may be 70% by weight to 100% by weight, 80% by weight to 100% by weight, 90% by weight to 100% by weight, 95% by weight to 100% by weight, 98% by weight to 100% by weight, or may be substantially 100% by weight.

[0040] The base polymer (A) may contain any other appropriate base polymer as long as the effect of the present invention is not impaired.

[0041] The preparation of the prepolymer type urethane polymer may be carried out by any suitable method as long as the method is a method of forming a prepolymer type urethane polymer by curing a urethane-based adhesive composition containing a urethane prepolymer and a polyfunctional isocyanate compound, within the scope of the present invention. For example, a method of applying a urethane-based adhesive composition containing a urethane prepolymer and a polyfunctional isocyanate compound onto any suitable substrate, heating and drying as necessary, curing as necessary, and preparing the prepolymer type urethane polymer in an adhesive layer formed on the substrate may be mentioned. The application method, heating and drying conditions, curing conditions, etc. may be appropriately adopted from methods generally known for forming an adhesive layer.

[0042] <A-2-1.ウレタンプレポリマー> The urethane prepolymer can be reacted with a polyfunctional isocyanate compound to form a prepolymer type urethane polymer.

[0043] The urethane prepolymer may be of only one type, or of two or more types.

[0044] The urethane prepolymer is preferably a polyurethane polyol, and more preferably is obtained by reacting a polyol with a polyfunctional isocyanate compound. The number average molecular weight Mn of the urethane prepolymer is, for example, 3,000 to 1,000,000.

[0045] The polyol includes at least one selected from the group consisting of polyester polyols and polyether polyols. Typically, the polyol is at least one selected from the group consisting of polyester polyols and polyether polyols. The polyester polyol may be only one type, or may be two or more types. The polyether polyol may be only one type, or may be two or more types.

[0046] As the polyester polyol, polyester polyols that can be normally used in the preparation of urethane prepolymers can be appropriately adopted. Examples of such polyester polyols include polyester polyols obtained by reacting an acid component with a glycol component. Examples of the acid component include terephthalic acid, adipic acid, azelaic acid, sebacic acid, phthalic anhydride, isophthalic acid, and trimellitic acid. Examples of the glycol component include ethylene glycol, propylene glycol, diethylene glycol, butylene glycol, 1,6-hexane glycol, 3-methyl-1,5-pentanediol, 3,3'-dimethylolheptane, polyoxyethylene glycol, polyoxypropylene glycol, 1,4-butanediol, neopentyl glycol, butylethylpentanediol, glycerin, trimethylolpropane, and pentaerythritol. In addition to the above, examples of the polyester polyol include polyester polyols obtained by ring-opening polymerization of lactones such as polycaprolactone, poly(β-methyl-γ-valerolactone) and polyvalerolactone.

[0047] The molecular weight of the polyester polyol that can be used ranges from low to high. The molecular weight of the polyester polyol is, for example, 100 to 100,000 in terms of number average molecular weight Mn, and preferably 100 to 10,000.

[0048] As the polyether polyol, polyether polyols that can be generally used in preparing urethane prepolymers can be appropriately adopted.As such polyether polyols, for example, polyether polyols containing two or more functional groups such as polyethylene glycol, polypropylene glycol, polytetramethylene glycol, etc. can be mentioned, and representatively, polyether polyols containing two or more groups of at least one type selected from the group consisting of methylene group and methine group can be mentioned.Polyether polyols can be used in combination by replacing a part of them with glycols such as ethylene glycol, polyamines such as ethylenediamine, etc., if necessary.

[0049] The molecular weight of the polyether polyol usable ranges from low to high. The number average molecular weight Mn of the polyether polyol is, for example, 100 to 100,000, and preferably 100 to 10,000.

[0050] One embodiment of the polyol is embodiment (A) which includes both a polyester polyol and a polyether polyol. In embodiment (A), typically the polyol comprises both a polyester polyol and a polyether polyol.

[0051] In embodiment (A), the content of the polyester polyol in the polyol is preferably 0.1% by weight to 99.9% by weight, may be 1% by weight to 99% by weight, may be 5% by weight to 95% by weight, may be 10% by weight to 90% by weight, may be 20% by weight to 80% by weight, or may be 30% by weight to 70% by weight.

[0052] In embodiment (A), the content ratio of polyether polyol in the polyol is preferably 0.1 wt% to 99.9 wt%, may be 1 wt% to 99 wt%, may be 5 wt% to 95 wt%, may be 10 wt% to 90 wt%, may be 20 wt% to 80 wt%, or may be 30 wt% to 70 wt%.

[0053] In embodiment (A), the polyether polyol is typically a polyether polyol containing two or more of at least one group selected from the group consisting of methylene and methine groups, and may be, for example, only a polyether polyol containing two of at least one group selected from the group consisting of methylene and methine groups, or may be composed of a polyether polyol containing two of at least one group selected from the group consisting of methylene and methine groups and a polyether polyol containing three or more of at least one group selected from the group consisting of methylene and methine groups. Examples of polyether polyols containing two of at least one group selected from the group consisting of methylene and methine groups include polyethylene glycol and polypropylene glycol. Examples of polyether polyols containing three or more of at least one group selected from the group consisting of methylene and methine groups include polytetramethylene glycol.

[0054] Another embodiment of the polyol is embodiment (B) which does not include a polyester polyol but includes a polyether polyol. In embodiment (B), typically the polyol consists of a polyether polyol.

[0055] In embodiment (B), the polyether polyol is typically a polyether polyol containing two or more of at least one group selected from the group consisting of methylene groups and methine groups, and may be, for example, only a polyether polyol containing two of at least one group selected from the group consisting of methylene groups and methine groups, or may be composed of a polyether polyol containing two of at least one group selected from the group consisting of methylene groups and methine groups and a polyether polyol containing three or more of at least one group selected from the group consisting of methylene groups and methine groups. Examples of polyether polyols containing two of at least one group selected from the group consisting of methylene groups and methine groups include polyethylene glycol and polypropylene glycol. Examples of polyether polyols containing three or more of at least one group selected from the group consisting of methylene groups and methine groups include polytetramethylene glycol.

[0056] The polyfunctional isocyanate compound to be reacted with the polyol to obtain the urethane prepolymer may be one type only, or two or more types may be used.

[0057] As the polyfunctional isocyanate compound, any suitable polyfunctional isocyanate compound that can be used in the preparation of a urethane prepolymer can be used. Examples of such polyfunctional isocyanate compounds include polyfunctional aliphatic isocyanate compounds, polyfunctional alicyclic isocyanate compounds, polyfunctional aromatic isocyanate compounds, and polyfunctional aromatic aliphatic isocyanate compounds.

[0058] Examples of polyfunctional aliphatic isocyanate compounds include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, 2,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.

[0059] Examples of polyfunctional alicyclic isocyanate compounds include 3-isocyanatemethyl-3,5,5-trimethylcyclohexyl isocyanate, 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), 1,4-bis(isocyanatemethyl)cyclohexane, 1,4-bis(isocyanatemethyl)cyclohexane, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated tolylene diisocyanate, and hydrogenated tetramethylxylylene diisocyanate.

[0060] Examples of polyfunctional aromatic isocyanate compounds include 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanate toluene, 1,3,5-triisocyanate benzene, 4,4'-diphenylether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, 4,4',4"-triphenylmethane triisocyanate, dianisidine diisocyanate, and xylylene diisocyanate.

[0061] Examples of polyfunctional aromatic aliphatic isocyanate compounds include ω,ω'-diisocyanate-1,3-dimethylbenzene, ω,ω'-diisocyanate-1,4-dimethylbenzene, ω,ω'-diisocyanate-1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, and 1,3-tetramethylxylylene diisocyanate.

[0062] Examples of the polyfunctional isocyanate compound include trimethylolpropane adducts of the various polyfunctional isocyanate compounds as described above, biuret compounds reacted with water, and trimers having an isocyanurate ring. These may also be used in combination.

[0063] To prepare a urethane prepolymer, the polyfunctional isocyanate compound is preferably used in an equivalent ratio such that the isocyanate group (NCO group) of the polyol is in excess of the hydroxyl group (OH group) of the polyol. Such an equivalent ratio of NCO group / OH group ([NCO] / [OH]) is preferably 1.01 to 5.0, more preferably 1.1 to 3.0, even more preferably 1.1 to 2.0, particularly preferably 1.1 to 1.8, and most preferably 1.2 to 1.6.

[0064] A catalyst may be used when preparing the urethane prepolymer. Any suitable catalyst may be used as long as it does not impair the effects of the present invention. Examples of such catalysts include tertiary amine catalysts and organometallic catalysts. The catalyst may be one type or two or more types.

[0065] Examples of the tertiary amine catalyst include triethylamine, triethylenediamine, and 1,8-diazabicyclo(5,4,0)-undecene-7 (DBU).

[0066] Examples of the organometallic catalyst include bismuth-based catalysts such as bismuth octoate, bismuth neodecanoate, bismuth naphthenate, and bismuth rosinate; tin-based catalysts such as dibutyltin dilaurate (DBTDL) and dioctyltin dilaurate (DOTDL); titanium-based catalysts such as dibutyltitanium dichloride, tetrabutyl titanate, butoxytitanium trichloride, and titanium tetraacetylacetonate; iron-based catalysts such as iron 2-ethylhexanoate and iron acetylacetonate; cobalt-based catalysts such as cobalt benzoate and cobalt 2-ethylhexanoate; zinc-based catalysts such as zinc octoate, zinc naphthenate, and zinc 2-ethylhexanoate; and zirconium-based catalysts such as zirconium naphthenate.

[0067] When a catalyst is used in preparing the urethane prepolymer, the amount of the catalyst used is preferably 0.0001 wt % to 1.0 wt %, more preferably 0.001 wt % to 1.0 wt %, still more preferably 0.003 wt % to 1.0 wt %, and particularly preferably 0.005 wt % to 1.0 wt %, based on the total amount of the polyol and the polyfunctional isocyanate compound.

[0068] When a catalyst is used in preparing the urethane prepolymer, the reaction temperature is preferably less than 100° C., and more preferably 85° C. to 95° C. If the temperature is 100° C. or higher, it may become difficult to control the reaction rate and crosslinked structure.

[0069] When preparing the urethane prepolymer, it is not necessary to use a catalyst. In this case, the reaction temperature is preferably 100° C. or higher, more preferably 110° C. or higher. When preparing the urethane prepolymer without a catalyst, it is preferable to carry out the reaction for 3 hours or more.

[0070] As a method for preparing the urethane prepolymer, any suitable method can be adopted as long as it does not impair the effects of the present invention. Examples of such methods include 1) a method in which the entire amount of a polyol, a catalyst, and a polyfunctional isocyanate compound is charged into a reaction vessel, and 2) a method in which a polyol and a catalyst are charged into a reaction vessel and a polyfunctional isocyanate compound is added. In the method 2), after the polyfunctional isocyanate compound is added, a polyol and a polyfunctional isocyanate compound may be further added.

[0071] Any suitable solvent may be used in preparing the urethane prepolymer, including, for example, methyl ethyl ketone, ethyl acetate, toluene, xylene, and acetone.

[0072] When preparing the urethane prepolymer, any suitable other components may be used within the scope of not impairing the effects of the present invention. Examples of other components include antioxidants, ultraviolet absorbers, light stabilizers, resin components, tackifiers, crosslinking retarders, inorganic fillers, organic fillers, metal powders, pigments, foils, softeners, antiaging agents, conductive agents, surface lubricants, leveling agents, corrosion inhibitors, heat stabilizers, polymerization inhibitors, and lubricants. The other components may be one type or two or more types. Among the other components, antioxidants, ultraviolet absorbers, and light stabilizers are one of the preferred embodiments.

[0073] Examples of the antioxidant include radical chain inhibitors and peroxide decomposers. Examples of the radical chain inhibitor include phenol-based antioxidants and amine-based antioxidants. Examples of the peroxide decomposers include sulfur-based antioxidants and phosphorus-based antioxidants.

[0074] Examples of the ultraviolet absorbing agent include benzophenone-based ultraviolet absorbing agents, benzotriazole-based ultraviolet absorbing agents, salicylic acid-based ultraviolet absorbing agents, anilide oxalate-based ultraviolet absorbing agents, cyanoacrylate-based ultraviolet absorbing agents, and triazine-based ultraviolet absorbing agents.

[0075] Examples of the light stabilizer include hindered amine light stabilizers.

[0076] <A-2-2. Polyfunctional Isocyanate Compound (B)> The urethane-based pressure-sensitive adhesive composition typically contains a polyfunctional isocyanate compound (B). The polyfunctional isocyanate compound (B) can react with the urethane prepolymer to form a prepolymer-type urethane polymer.

[0077] The polyfunctional isocyanate compound (B) may be only one kind or two or more kinds.

[0078] As the polyfunctional isocyanate compound (B), any suitable polyfunctional isocyanate compound that can be used in the urethanization reaction can be adopted. For example, the polyfunctional isocyanate compound that can be used in the preparation of the urethane prepolymer described above can be adopted.

[0079] The equivalent ratio ([NCO] / [OH]) of the NCO group (isocyanate group) of the polyfunctional isocyanate compound (B) to the OH group (hydroxyl group) of the urethane prepolymer has a lower limit that is preferably 0.5 or more, and may be 1.0 or more, 1.5 or more, 2.0 or more, 2.5 or more, 3.0 or more, 3.1 or more, 3.2 or more, 3.3 or more, 3.4 or more, 3.5 or more. If the lower limit of the above equivalent ratio ([NCO] / [OH]) is within the above range, the effects of the present invention can be more expressed. If the lower limit of the above equivalent ratio ([NCO] / [OH]) is too small, there is a possibility that the peelability over time may decrease.

[0080] The upper limit of the equivalent ratio ([NCO] / [OH]) of the NCO group (isocyanate group) of the polyfunctional isocyanate compound (B) to the OH group (hydroxyl group) of the urethane prepolymer is preferably 5.0 or less, may be 4.8 or less, may be 4.7 or less, may be 4.6 or less, may be 4.5 or less, may be 4.4 or less, or may be 4.3 or less. If the upper limit of the equivalent ratio ([NCO] / [OH]) is within the above range, the effects of the present invention can be more effectively exhibited. If the upper limit of the equivalent ratio ([NCO] / [OH]) is too large, there is a risk of glue residue being generated from the adhesive layer.

[0081] The equivalent ratio ([NCO] / [OH]) of the NCO group (isocyanate group) of the polyfunctional isocyanate compound (B) to the OH group (hydroxyl group) of the urethane prepolymer is preferably in the range of 0.5 to 5.0, may be 1.0 to 4.8, may be 1.0 to 4.7, may be 1.0 to 4.6, may be 1.5 to 4.6, may be 2.0 to 4.6, may be 2.5 to 4.6, may be 3.0 to 4.6, may be 3.1 to 4.6, may be 3.2 to 4.6, may be 3.3 to 4.5, may be 3.4 to 4.4, or may be 3.5 to 4.3. If the equivalent ratio ([NCO] / [OH]) is within the above range, the effect of the present invention can be more effectively exhibited. If the equivalent ratio ([NCO] / [OH]) is too small, there is a risk of the light peelability decreasing over time. If the above equivalent ratio ([NCO] / [OH]) is too large, there is a risk of glue residue being generated from the adhesive layer.

[0082] The content of the polyfunctional isocyanate compound (B) in the urethane-based pressure-sensitive adhesive composition is preferably 1.0 to 15 parts by weight, may be 2.0 to 14 parts by weight, may be 2.5 to 13 parts by weight, may be 3.0 to 12 parts by weight, may be 3.5 to 11 parts by weight, may be 4.0 to 10 parts by weight, may be 4.5 to 9.5 parts by weight, may be 5.0 to 9.0 parts by weight, may be 5.5 to 8.5 parts by weight, based on 100 parts by weight of the urethane prepolymer. If the content of the polyfunctional isocyanate compound (B) is within the above range, the effects of the present invention can be more expressed. If the content of the polyfunctional isocyanate compound (B) is too small, there is a possibility that the light peelability may decrease over time. If the content of the polyfunctional isocyanate compound (B) is too large, there is a possibility that paste residues may be generated from the pressure-sensitive adhesive layer.

[0083] <A-2-3. Catalyst> The urethane-based pressure-sensitive adhesive composition may use a catalyst to promote the reaction between the urethane prepolymer and the polyfunctional isocyanate compound (B). As such a catalyst, any appropriate catalyst can be used as long as the effects of the present invention are not impaired. Examples of such a catalyst include the catalysts that can be used for the preparation of the urethane prepolymer described above.

[0084] When using a catalyst for the reaction between the urethane prepolymer and the polyfunctional isocyanate compound (B), the content of the catalyst in the urethane-based pressure-sensitive adhesive composition is preferably 0.0001 to 1.0 part by weight, more preferably 0.001 to 1.0 part by weight, still more preferably 0.003 to 1.0 part by weight, and particularly preferably 0.005 to 1.0 part by weight, based on 100 parts by weight of the base polymer (A).

[0085] <A-2-4. Silicone-based compound (C)> The urethane-based pressure-sensitive adhesive composition contains a silicone-based compound (C). The silicone-based compound (C) may be only one kind or two or more kinds.

[0086] The content of the silicone compound (C) in the urethane-based pressure-sensitive adhesive composition is preferably 1.0 parts by weight or less, may be 0.9 parts by weight or less, may be 0.8 parts by weight or less, may be 0.7 parts by weight or less, may be 0.01 to 0.6 parts by weight, may be 0.1 to 0.55 parts by weight, or may be more than 0.2 parts by weight and less than 0.5 parts by weight, based on 100 parts by weight of the base polymer (A). If the content of the silicone compound (C) is within the above range, the effects of the present invention can be more effectively achieved. If the content of the silicone compound (C) is too low, there is a risk that excellent light peelability cannot be achieved. If the content of the silicone compound (C) is too high, there is a risk that excellent low-staining properties cannot be achieved.

[0087] The silicone compound (C) has a skeleton derived from a monomer (a) whose corresponding homopolymer has a Tg (glass transition temperature) of 80° C. or higher. By employing a silicone compound having a skeleton derived from a monomer (a) whose corresponding homopolymer has a Tg (glass transition temperature) of 80° C. or higher as the silicone compound (C), the effects of the present invention can be more effectively achieved.

[0088] Silicone compound (C) has a skeleton derived from monomer (a) whose corresponding homopolymer has a Tg (glass transition temperature) of 80° C. or higher, and thus has a high Tg polymer skeleton introduced therein, making it a compound having a silicone skeleton and a high Tg skeleton introduced therein. The introduction of the silicone skeleton results in excellent easy releasability, and in addition, the introduction of the high Tg polymer skeleton increases the hardness of the pressure-sensitive adhesive layer near the interface with the adherend, and it is presumed that these actions combine to achieve both excellent easy releasability and excellent low contamination.

[0089] For the Tg of a homopolymer, a value described in a publicly known document may be used. For example, the value described in "Polymer Handbook" (3rd Edition, John Wiley & Sons, Inc., 1989) may be used. If multiple values ​​are described in the "Polymer Handbook," the conventional value is used. For a monomer not described in the "Polymer Handbook," the catalog value of the monomer manufacturer is used. For the glass transition temperature Tg of a homopolymer of a monomer not described in the "Polymer Handbook" and for which no catalog value is provided by the monomer manufacturer, the value obtained by the measurement method described in JP-A-2007-51271 is used.

[0090] Examples of the monomer (a) having a Tg of 80° C. or higher in the corresponding homopolymer include (meth)acrylic acid and (meth)acrylic acid esters having a Tg of 80° C. or higher in the corresponding homopolymer. Examples of the (meth)acrylic acid esters having a Tg of 80° C. or higher in the corresponding homopolymer include methyl methacrylate, t-butyl methacrylate, and cyclohexyl methacrylate.

[0091] The silicone-based compound (C) may further contain a monomer (b) whose corresponding homopolymer has a Tg of 60° C. or more and less than 80° C. When the silicone-based compound (C) further contains such a monomer (b), the effects of the present invention can be more effectively exhibited.

[0092] Examples of the monomer (b) having a Tg of the corresponding homopolymer of 60° C. or more and less than 80° C. include (meth)acrylic acid esters having a Tg of the corresponding homopolymer of 60° C. or more and less than 80° C. Examples of the (meth)acrylic acid esters having a Tg of the corresponding homopolymer of 60° C. or more and less than 80° C. include ethyl methacrylate.

[0093] Silicone compounds (C) are made up of M units (R 3Si-O-) (a unit in which three of the four bonds of Si are organic groups R (typically methyl groups) and one is bonded to an oxygen atom), D unit (R 2 Si(-O-) 2 ) (a unit in which two of the four bonds of Si are organic groups R (typically methyl groups) and two are bonded to oxygen atoms), T unit (R-Si(-O-) 3 ) (a unit in which one of the four bonds of Si is an organic group R (typically a methyl group) and three are bonded to oxygen atoms), and Q units (Si(-O-) 4 ) (a unit in which all four of the four bonds of Si are bonded to an oxygen atom). One preferred embodiment of the silicone compound (C) includes an M unit, a D unit, and a T unit as basic units containing a silicon atom.

[0094] The silicone compound (C) may have an alkylene oxide structure. Examples of such alkylene oxide structures include an ethylene oxide structure and a propylene oxide structure. The alkylene oxide structure may be one type or two or more types. When the silicone compound (C) contains an alkylene oxide structure, the effects of the present invention can be more effectively exhibited.

[0095] One preferred embodiment of the silicone-based compound (C) has a skeleton derived from a monomer (a) whose corresponding homopolymer has a Tg (glass transition temperature) of 80° C. or more, and further has a skeleton derived from a monomer (b) whose corresponding homopolymer has a Tg of 60° C. or more and less than 80° C. Another preferred embodiment of the silicone-based compound (C) has a skeleton derived from a monomer (a) whose corresponding homopolymer has a Tg (glass transition temperature) of 80° C. or more, and further has an alkylene oxide structure. Yet another preferred embodiment of the silicone-based compound (C) has a skeleton derived from a monomer (a) whose corresponding homopolymer has a Tg (glass transition temperature) of 80° C. or more, and further has a skeleton derived from a monomer (b) whose corresponding homopolymer has a Tg of 60° C. or more and less than 80° C., and further has an alkylene oxide structure.

[0096] The silicone-based compound (C) may not contain a fluorine atom. By not containing a fluorine atom, it may be possible to comply with PFAS regulations.

[0097] <A-2-5. Other Components> The urethane-based pressure-sensitive adhesive composition may contain any suitable other components as long as the effects of the present invention are not impaired. Examples of such other components include solvents, antistatic agents, crosslinking accelerators, silane coupling agents, fatty acid esters, antioxidants, ultraviolet absorbers, light stabilizers, resin components, tackifiers, crosslinking retarders, inorganic fillers, organic fillers, metal powders, colorants (such as pigments and dyes), chain transfer agents, plasticizers, softeners, anti-aging agents, conductive agents, foils, surface lubricants, leveling agents, corrosion inhibitors, heat stabilizers, polymerization inhibitors, and lubricants. The other components may be only one kind or two or more kinds. The content ratio of the other components in the urethane-based pressure-sensitive adhesive composition may be set to any appropriate content ratio according to the purpose as long as the effects of the present invention are not impaired.

[0098] ≪A-3. Release Liner≫ The surface protection film of the present invention may contain a release liner. As described above, the release liner is usually provided on the surface opposite to the base material of the pressure-sensitive adhesive layer.

[0099] Examples of the release liner include a release liner in which the surface of a base material (liner base material) such as paper or a plastic film is silicone-treated, and a release liner in which the surface of a base material (liner base material) such as paper or a plastic film is laminated with a polyolefin-based resin.

[0100] Examples of plastic films usable as liner substrates include polyethylene films, polypropylene films, polybutene films, polybutadiene films, polymethylpentene films, polyvinyl chloride films, vinyl chloride copolymer films, polyethylene terephthalate films, polybutylene terephthalate films, polyurethane films, and ethylene-vinyl acetate copolymer films.

[0101] The thickness of the release liner is preferably from 1 μm to 500 μm, more preferably from 3 μm to 450 μm, still more preferably from 5 μm to 400 μm, and particularly preferably from 10 μm to 300 μm.

[0102] ≪≪B.Applications≫≫ The surface protection film according to the embodiment of the present invention is typically attached to an exposed surface of an optical or electronic component in the manufacturing process of the optical or electronic component to prevent the surface of the optical or electronic component from being scratched during processing, assembly, inspection, transportation, etc., and can be suitably used for surface protection of the optical or electronic component. The optical component of the present invention includes the surface protection film of the present invention. The electronic component of the present invention includes the surface protection film of the present invention. EXAMPLES

[0103] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. The test and evaluation methods in the examples are as follows. The term "parts" means "parts by weight" unless otherwise specified, and the term "%" means "% by weight" unless otherwise specified.

[0104] <Peeling strength against acrylic plate after leaving for 30 minutes at 23°C (I)> The surface protection film (width 25 mm x length 140 mm) from which the release liner had been peeled off was attached to an acrylic plate (Acrylite L, manufactured by Mitsubishi Chemical Corporation) with one round trip of a 2 kg hand roller. After that, the film was left at an environmental temperature of 23°C for 30 minutes to prepare an evaluation sample. Using the obtained evaluation sample, the peeling force (I) from the acrylic plate after leaving it at a temperature of 23°C for 30 minutes was measured using a tensile tester. The tensile tester used was Shimadzu Corporation's product name "Autograph AG-Xplus HS 6000mm / min high-speed model (AG-50NX plus)". After setting the evaluation sample on the tensile tester, the tensile test was started. The conditions for the tensile test were a temperature of 23°C, a peeling angle of 180 degrees, and a peeling speed (tensile speed) of 300 mm / min. The load when the surface protection film was peeled off from the acrylic plate was measured, and the average load at that time was taken as the peeling force (I) from the acrylic plate after leaving the surface protection film at a temperature of 23°C for 30 minutes.

[0105] <Peeling strength against acrylic plate after leaving at 50℃ for 1 day (II)> The surface protection film (width 25 mm x length 140 mm) from which the release liner had been peeled off was attached to an acrylic plate (Acrylite L, manufactured by Mitsubishi Chemical Corporation) with one round trip of a 2 kg hand roller. After that, the film was left at an environmental temperature of 50°C for one day to prepare an evaluation sample. Using the obtained evaluation sample, the peel strength (II) from the acrylic plate after leaving it at a temperature of 50°C for one day was measured using a tensile tester. The tensile tester used was Shimadzu Corporation's product name "Autograph AG-Xplus HS 6000mm / min high-speed model (AG-50NX plus)". After setting the evaluation sample on the tensile tester, the tensile test was started. The conditions for the tensile test were a temperature of 23°C, a peel angle of 180 degrees, and a peel speed (tensile speed) of 300 mm / min. The load when the surface protection film was peeled off from the acrylic plate was measured, and the average load at that time was taken as the peel strength (II) from the acrylic plate after leaving the surface protection film at a temperature of 50°C for one day.

[0106] <Rate of increase in peeling force over time> The rate of increase in peel strength with time from the acrylic plate peel strength (I) to the acrylic plate peel strength (II) was calculated by the following formula. Peel strength increase rate over time (%) = (peel strength from acrylic plate (II) / peel strength from acrylic plate (I)) x 100 (%)

[0107] <Residual adhesion rate to acrylic board> The surface protection film from which the release liner had been removed was applied to the entire surface of an acrylic plate (Acrylite L, manufactured by Mitsubishi Chemical Corporation) using one reciprocating motion with a 2 kg hand roller, and after leaving it at a temperature of 23°C for 24 hours, the surface protection film was peeled off using a tensile tester (Shimadzu Corporation's product name "Autograph AG-Xplus HS 6000mm / min high-speed model (AG-50NX plus)") at a peel angle of 180 degrees and a peel speed (tensile speed) of 300 mm / min. Then, a 19 mm wide No. 31B tape (manufactured by Nitto Denko Corporation, substrate thickness = 25 μm, total thickness = 53 μm) cut to a length of 150 mm was applied to the peeled surface of the acrylic plate using one reciprocating motion with a 2 kg hand roller at a temperature of 23°C. After leaving it at a temperature of 23°C for 30 minutes, the peel force (A) was measured by peeling at a temperature of 23°C, a peel angle of 180 degrees, and a tensile speed of 300 mm / min using a tensile testing machine (Shimadzu Corporation, product name "Autograph AG-Xplus HS 6000 mm / min high speed model (AG-50NX plus)"). Separately, an adhesive tape (product name "No. 31B", manufactured by Nitto Denko Corporation, substrate thickness = 25 μm, total thickness = 53 μm) was similarly attached to an acrylic plate that had not had the surface protective film attached or peeled off as described above, and after leaving it at a temperature of 23°C for 30 minutes, the peel force (B) was measured when it was peeled off at a peel angle of 180 degrees and a peel speed of 300 mm / min. The residual adhesion rate to the acrylic plate was calculated using the following formula. Residual adhesion rate to acrylic plate (%) = (peel strength (A) / peel strength (B)) x 100 (%)

[0108] <Cutter glue residue evaluation> The release liner was removed from the surface protection film (25 mm wide x 140 mm long), and the adhesive layer side of the film was cut 1 cm into the center with a cutter blade at 90 degrees. The film was evaluated according to the following criteria. ◯: No glue residue was visually observed to have fallen off. △: Falling off of glue residue was observed.

[0109] [Production Example 1]: Production of urethane prepolymer Into a polymerization experiment apparatus equipped with a 1L round-bottom separable flask, a separable cover, a separating funnel, a thermometer, a nitrogen inlet tube, a Liebig condenser, a vacuum seal, a stirring rod, and a stirring blade, 197 g of polypropylene glycol (product name "Sannyx PP-2000", manufactured by Sanyo Chemical Industries, Ltd.), 197 g of polyester polyol (product name "Kuraray Polyol P-2010", manufactured by Kuraray Co., Ltd.), 110 g of toluene (manufactured by Tosoh Corporation) as a solvent, and 0.041 g of dibutyltin dilaurate (IV) (manufactured by Wako Pure Chemical Industries, Ltd.) as a catalyst were added, and nitrogen replacement was performed at room temperature for 1 hour while stirring. Then, under nitrogen flow, 33.5 g of hexamethylene diisocyanate (product name "HDI", manufactured by Tosoh Corporation) was added while stirring, and the solution temperature in the experimental apparatus was controlled to 90 ± 2 ° C. in a water bath and held for 4 hours, after which 44 g of polypropylene glycol (product name "GP1000", manufactured by Sanyo Chemical Industries Co., Ltd.) was added, and the solution temperature in the experimental apparatus was controlled to 90 ± 2 ° C. in a water bath and held for 2 hours, after which 25.4 g of hexamethylene diisocyanate (product name "HDI", manufactured by Tosoh Corporation) was added, and the solution temperature in the experimental apparatus was controlled to 90 ± 2 ° C. in a water bath and held for 2 hours to obtain a urethane prepolymer solution A. In addition, toluene was appropriately added dropwise during the polymerization to control the temperature during polymerization and to prevent a decrease in stirrability due to an increase in viscosity. The total amount of toluene added was 380 g. The solid concentration of the urethane prepolymer solution A was 50% by weight.

[0110] [Example 1] A urethane-based adhesive composition was obtained by diluting 100 parts by weight of the urethane prepolymer solution A, 3.0 parts by weight of a multifunctional isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.4 parts by weight of a silicone-based compound (MEGAFACE EFS-132, manufactured by DIC Corporation) having a skeleton derived from methyl methacrylate (a monomer whose corresponding homopolymer has a Tg of 80°C or higher) as a silicone-based compound, and 0.5 parts by weight of Irganox1010 (manufactured by BASF Corporation) as an antioxidant with ethyl acetate to a total solids content of 50% by weight. The obtained urethane-based adhesive composition was applied to a PET film (product name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) so that the thickness after drying was 75 μm, and cured and dried under conditions of a drying temperature of 130° C. and a drying time of 3 minutes to prepare an adhesive layer composed of an acrylic adhesive. Next, the silicone-treated surface of a release liner (product name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of a polyester resin having a thickness of 25 μm and one side of which was silicone-treated was laminated to the surface of the obtained adhesive layer to obtain a surface protection film (1). Aging was performed at room temperature for 5 days, and evaluation was performed. The results are shown in Table 1.

[0111] [Examples 2 to 15] Surface protection films (2) to (15) were obtained in the same manner as in Example 1, except that the amount of the polyfunctional isocyanate compound and the amount of the silicone compound were changed as shown in Table 1. Aging was carried out at room temperature for 5 days, and evaluation was carried out. The results are shown in Table 1.

[0112] [Comparative Example 1] A surface protective film (C1) was obtained in the same manner as in Example 1, except that 0.4 parts by weight of methyl methacrylate was used instead of 0.4 parts by weight of a silicone-based compound having a skeleton derived from methyl methacrylate (a monomer whose corresponding homopolymer has a Tg of 80° C. or higher). The film was aged at room temperature for 5 days and then evaluated. The results are shown in Table 1.

[0113] [Comparative Example 2] A surface protective film (C2) was obtained in the same manner as in Example 1, except that 0.4 parts by weight of silicone oil (trade name "KF-615A", manufactured by Shin-Etsu Chemical Co., Ltd.) was used instead of 0.4 parts by weight of a silicone compound having a skeleton derived from methyl methacrylate (a monomer whose corresponding homopolymer has a Tg of 80°C or higher). The film was aged at room temperature for 5 days and then evaluated. The results are shown in Table 1.

[0114] [Table 1]

[0115] [Examples 16 to 30] For each of the surface protection films (1) to (15) obtained in Examples 1 to 15, the release liner was peeled off and the pressure-sensitive adhesive layer side was attached to a polarizing plate (manufactured by Nitto Denko Corporation, product name "TEG1465DUHC"), which is an optical component, to obtain an optical component with a surface protection film attached.

[0116] [Examples 31 to 45] For each of the surface protection films (1) to (15) obtained in Examples 1 to 15, the release liner was peeled off and the adhesive layer side was attached to a conductive film (manufactured by Nitto Denko Corporation, product name "ELECRYSTA V270L-TFMP"), which is an electronic component, to obtain an electronic component with a surface protection film attached thereto. [Industrial Applicability]

[0117] The surface protective film of the present invention can be used for any suitable application, and is preferably used in the fields of optical members and electronic members. [Explanation of symbols]

[0118] 1 Base material layer 2 Adhesive layer 3 Release Liner 10 Surface protection film

Claims

1. A surface protection film comprising a substrate and a pressure-sensitive adhesive layer, the pressure-sensitive adhesive layer is made of a urethane-based pressure-sensitive adhesive, the urethane-based pressure-sensitive adhesive is formed from a urethane-based pressure-sensitive adhesive composition, The urethane-based pressure-sensitive adhesive composition contains a base polymer (A), a polyfunctional isocyanate compound (B), and a silicone-based compound (C), The base polymer (A) comprises a urethane prepolymer, The silicone-based compound (C) is a silicone-based compound having a skeleton derived from a monomer (a) whose corresponding homopolymer has a Tg of 80° C. or higher. Surface protection film.

2. 2. The surface protective film according to claim 1, wherein an equivalent ratio ([NCO] / [OH]) of the NCO group of the polyfunctional isocyanate compound (B) to the OH group of the urethane prepolymer is 1.0 or more.

3. 2. The surface protective film according to claim 1, wherein an equivalent ratio ([NCO] / [OH]) of the NCO group of the polyfunctional isocyanate compound (B) to the OH group of the urethane prepolymer is 4.6 or less.

4. The surface protective film according to claim 1 , wherein the content of the silicone compound (C) in the urethane-based pressure-sensitive adhesive composition is 0.7 parts by weight or less per 100 parts by weight of the base polymer (A).

5. An optical member comprising the surface protective film according to claim 1 .

6. An electronic component comprising the surface protection film according to claim 1 .

Citation Information

Patent Citations

  • Surface protection film

    JP6613516B2